Historitas Agama Mesir Kuno Dalam Perspektif A-Qur’an - Fitriani Fitriani; Anggita Nabila (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Ancient Egyptian civilization is very often talked about. This is not surprising given the great legacy of the ancient Egyptian leaders. What is taken for discussion is the belief system of the ancient Egyptian people. There are so many things related to Egypt in terms of their civilization which can be said to be very large and extraordinary at that time. The relics that are considered the most historic are the Pyramids which were built using very heavy stone. Then, another thing that was discussed was about the belief of the Egyptian people in the existence of many gods and recognizing and respecting the sanctity of certain animals. In this paper, using a qualitative approach to the method of literature study, through exploration of various data such as books, journals and others. The result of this study is to find that ancient Egyptian folk beliefs were more focused on the number of gods and considered that Pharaoh was the representative of the gods and as a means of intermediary between the people and the gods. Pharaohs who are believed to have sacred powers to intercede for their people with the goddess in the field of knowledge, the ancient Egyptians focused on mathematics and astronomy, they also used the calendar to calculate planting time, the language used comes from the ancient Greek language contained in the covenant called stone. the ancient rosetta hunting system, still uses the hunting system, still uses weapons such as spears and arrows and farms on the banks of the nile because apart from that the area is dry because of the desert, social life is divided into 3 castes, namely upper caste, middle caste and lower caste. Keywords: Ancient Egypt, civilization, religion, history.